Activating the Electrocatalysis of MoS2 Basal Plane for Hydrogen Evolution via Atomic Defect Configurations. Issue 22 (2nd May 2022) - Liu, Xiao; Jiang, Xingxing; Shao, Gonglei; Xiang, Haiyan; Li, Zhiwei; Jin, Yuanyuan; Chen, Yang; Jiang, Huili; Li, Huimin; Shui, Jianglan; Feng, Yexin; Liu, Song
Abstract: Point defects of heteroatoms and vacancies can activate the inert basal plane of molybdenum sulfide (MoS2 ) to improve its performance on catalyzing the hydrogen evolution reaction (HER). However, the synergy between heteroatoms and vacancies is still unclear. Here, a chemical vapor deposition‐assisted in situ vanadium (V) doping method is used to synthesize monolayer MoS2 with abundant and tunable vacancies and V‐dopants in the lattice. Ten delicate defect configurations are prepared to provide a complex system for the relationship investigation between microstructure and catalytic performance. The combination of on‐chip electrochemical tests and theoretical calculations indicates that the HER performance greatly depends on the type and amount of defect configurations. The optimal configuration is that three V atoms are aggregated and accompanied by abundant sulfur vacancies, in which, H atoms directly interact with Mo and V atoms to form the most stable metal‐bridge structure. The on‐chip measurements also confirm that the sample with high concentrations of this type of defect configuration exhibits the best catalytic performance, indicating the efficient synergy in the optimal configuration. The revealed effects of defect configurations are expected to inspire the design and regulation of high‐efficiency 2D catalysts. Abstract : V‐doped MoS2 with different V doping concentration are prepared by adjusting V/Mo in liquid precursors. Abundant vacancies are induced by V dopants to form diverse atomic defect configurations, providing a fertile H adsorption site to enhance the hydrogen evolution reaction activity of MoS2 . The association between defect configurations and catalytic performance is investigated combining electrochemical testing with theoretical calculations.